The Role of Innovation in the Future PV and Storage Markets - Silva, J.; Oliveira, S.; Távora, G.; Mendonça, S. (Proceedings 31st European Photovoltaic Solar Energy Conference and Exhibition, 2015)
The trends of research and innovation in photovoltaic (PV) and battery technologies are the focus of this work. The possible interactions between these two fields are also explored. Patents are employed as an innovation indicator. The approach helps to identify the most dynamic technology branches and to point-out the players that have contributed the most to the innovation in these areas. In spite of some heterogeneity, both PV and battery fields show a growth patterns in terms of filled patents. The number of patents filled on both PV + batteries is still small, indicating that the innovation bonds between the two fields are still weak and that the cross-enabling dynamics between complementary technologies remains a bottleneck for the renewables agenda as a whole.